Male Circumcision in India: Some Considerations from the West (Bangladesh Journal of Bioethics, 2013)
In this work, I will analyse why Indian authorities find it so difficult to publicly acknowledge the medical benefits of Male Circumcision (MC). In doing so, the medical evidence in favour of the practice, as well as the moral duties that governing authorities have towards their citizens shall be taken to the fore. In addition to this argument, a brief explanation of the cultural dimension that refuses to evaluate the medical dimension of MC a priori shall be taken into account and, in relation to that, a parallel with the past and present Western tradition will be drawn, putting forward the conclusion that both contexts do not provide satisfactory justification for banning MC nor more relevantly for the Indian scenario can any cultural background represent a convincing argument against the public acknowledgement of the medical advantages provided by MC. DOI: http://dx.doi.org/10.3329/bioethics.v4i1.14263 Bangladesh Journal of Bioethics 2013; 4(1):2-8